Usos, lenguajes y formatos en las Redes Sociales de los zapatos de moda: @flabelus - Parres, Bienvenida Araceli; Infante, Sara; Martínez, Rut (Cuadernos de Documentación Multimedia, 2026)
This article proposes a study focused on the uses, formats, and languages of the content published on the Instagram social network by the @Flabelus account, a Spanish footwear brand founded in 2020 during the COVID-19 pandemic that has 390,000 followers on Instagram.In a context where social networks function simultaneously as a space for communication, a living archive and an ephemeral repository of interactions between brands and users, this analysis positions Flabelus’ content as cultural documents representing the brand universe as a link to the digital and communication community in more than 40 markets. The distribution of the product across four continents worldwide implies a transnational audience, which requires Flabelus to design discursive and aesthetic strategies linking visual, sound and narrative codes to the logic of Instagram, which brings together the practices of all social networks. The study analyses a qualitative sample of posts extracted from this social network using Transana software, which will be examined through discourse analysis to determine (1) what languages—visual, verbal, audio—it uses to address its audiences; (2) what formats are most effective for the digital positioning of the product; and (3) how the brand uses social media. Preliminary results suggest that the use of aesthetics, format type and linguistic register are strategically tailored to a global audience, maintaining consistency with the brand’s values.